Phase-Sensitive Radar Using ADALM-Pluto SDR and Cantenna for Sub-Millimeter Displacement Measurement - Eril Mozef; Ridho Shofwan Rasyid; Enceng Sulaeman; Tiyo Rizky Mulyana; Fahrizal Al Farik; Thaskia Qolbi Junjunan (National Research and Innovation Agency, 2025)
The capability of phase-sensitive radar to detect sub-millimeter displacement has been widely demonstrated, enabling a range of applications such as structural vibration monitoring, human vital-sign detection, gesture sensing, and precision motion tracking. In these domains, particularly in non-contact human respiratory monitoring, conventional phase-sensitive radar systems offer key advantages, including high phase stability, robust performance under non-ideal lighting or environmental conditions, and the ability to operate without physical contact. These strengths make them effective for capturing small periodic chest movements required for accurate respiratory assessment. However, conventional hardware implementations often suffer from limited flexibility, higher development cost, and increased design complexity. These constraints motivate the shift toward software-defined radio (SDR) solutions, which provide reconfigurability, simplified prototyping, and significantly lower cost while retaining the essential phase-sensitive capabilities. This motivation forms the basis of the present research. This study realizes a phase-sensitive radar using an ADALM-Pluto SDR operating at 2.45 GHz with a cantenna antenna configuration. Compared with previous SDR-based works that focus primarily on Doppler vital-sign extraction or require more elaborate RF front-ends, the proposed system emphasizes displacement-resolution enhancement through careful phase processing while maintaining minimal hardware complexity. The combination of a compact SDR platform, simple antenna structure, and optimized signal processing pipeline yields a practical and accessible radar prototype. Experimental results demonstrate that the proposed system achieves a displacement resolution of 0.5 mm, meeting the requirements for developing a reliable respiratory-monitoring application and confirming the suitability of SDR-based phase-sensitive radar for low-cost biomedical sensing.